Analytical solution of non-exponential decay in a simple resistor-capacitor circuit using the Lambert-Tsallis Wq function - L.A.B. Ramos; R.V. Ramos (Revista Brasileira de Ensino de Física)
In this work, using the Lambert-Tsallis Wq function, we present the analytical solution for the non-exponential decay in a simple electrical circuit composed by two resistors, two capacitors and a DC power supply. Additionally, it is shown that, in a particular case, the circuit equation assumes the form of Fermat’s equation, ax + bx = cx, allowing to observe a physical behavioral difference depending on whether the capacitances values are algebraic or transcendental numbers.